Le dol d'un locateur peut·il être sanctionné par une diminution du loyer? - Rousseau-Houle, Thérèse (Les Cahiers de droit, 1977)
A lessee requests a reduction of his rent in reply to a claim for unpaid rents. His request is based upon the lessor's false representations as to the business a building was liable to bring to lessee's restaurant situated therein. The principal claim was sustained and the cross-claim rejected. The only recourse open in case of fraudulent manoeuvres would have been an action in nullity.